2020
DOI: 10.3390/molecules25061318
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Evaluation and Anti-Angiogenic Effects of Two Furano-Sesquiterpenoids from Commiphora myrrh Resin

Abstract: Commiphora myrrh resin (Myrrh) has been used in traditional Arabic medicine to treat various inflammatory diseases. Two furano-sesquiterpenoids, 2-methoxyfuranodiene (CM1) and 2-acetoxyfuranodiene (CM2), were isolated from the chloroform fraction of the ethanolic extract of Arabic Commiphora myrrh resin. The cytotoxicity of the compounds was evaluated using human liver carcinoma, breast cancer cells (HepG2 and MCF-7, respectively) and normal human umbilical vein endothelial cells (HUVECs) cell lines. The devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 57 publications
(61 reference statements)
2
23
0
Order By: Relevance
“…The effects of HRG-Au and AP-HRG-Au on the cell cycle distribution of MCF-7 cells were determined by flow cytometric analysis as earlier reported. 41 Briefly, treated or untreated cells were harvested and washed with cold PBS twice. Following fixation with 70% ethanol at 4 °C for 4 h, cells were stained with freshly prepared DNA-staining solution containing propidium iodide (PI, 50 μg/mL) and RNase A (100 μg/mL).…”
Section: Experimental Detailsmentioning
confidence: 99%
“…The effects of HRG-Au and AP-HRG-Au on the cell cycle distribution of MCF-7 cells were determined by flow cytometric analysis as earlier reported. 41 Briefly, treated or untreated cells were harvested and washed with cold PBS twice. Following fixation with 70% ethanol at 4 °C for 4 h, cells were stained with freshly prepared DNA-staining solution containing propidium iodide (PI, 50 μg/mL) and RNase A (100 μg/mL).…”
Section: Experimental Detailsmentioning
confidence: 99%
“…Cell viability MTT assay was carried out according to Alqahtani et al [ 24 ]. In brief, A549 (lung), MCF-7 (breast), and HepG2 (liver) cancer cells were harvested, counted, and plated on the bottom of a 24-well plate (5 x 10 4 cells/well) for 24 h to allow for attachment.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, a recent GC-mass spectroscopic study was performed on MEO and revealed that 2-acetoxy-furano-diene (26.82%) was the major volatile component of this essential oil [34]. and antiangiogenic effects [36]. In addition, MEO was found to be effective against some cancer cell lines, including liver, breast, and colon cancer cell lines.…”
Section: Biological Activity Of Myrrh (Commiphora Myrrha) Essential Oilmentioning
confidence: 99%
“…Rhizomes are light brown and covered with MEO was subjected to a systematic study to reveal its biological activity. For example, a fraction of MEO contains some volatile sesquiterpene compounds that show anti-Alzheimer's disease [35] and antiangiogenic effects [36]. In addition, MEO was found to be effective against some cancer cell lines, including liver, breast, and colon cancer cell lines.…”
Section: Biological Activity Of Ginger (Zingiber Officinale)mentioning
confidence: 99%